Adolescent aggression and suicidality: A meta-analysis. (May 2022) - Detullio, David; Kennedy, Tom D.; Millen, Danielle H.
Abstract: Since the 1900s it has been theorized that aggression and suicidality are associated with each other. Research has provided empirical support for such theories, including the specific mechanisms which may explain the association between the two variables. While some researchers have begun examining the specific features of aggression and suicidality that are related to each other, this meta-analysis sought to provide an overall estimate of the association between the two variables among adolescents in order to understand the relationship as a whole. Research reports were retrieved by searching databases (e.g., PsycINFO) and reviewing subsequent reference lists. After reviewing potential research reports, 122 ( N = 182, 623) were selected, and 142 correlations were included in the random-effects meta-analytic model. The average correlation between aggression and suicidality was found to be 0.20, z = 14.53, p < 0.001, 95% CI [0.17, 0.23], I 2 = 95.0%, and three moderators were found to significantly influence effect sizes. This meta-analysis demonstrates that there can be a moderate correlation between aggression and suicidality among adolescents, however the average effect size might be smaller or larger depending on methodological features of individual research reports. The observed average correlation may also be a conservative estimate due to the analytic choices for this study. Nonetheless, the results from this study could provide a general sense of the relationship between aggression and suicidality in adolescents.